Cross-Kingdom Extracellular Vesicles EV-RNA Communication as a Mechanism for Host–Pathogen Interaction - Munhoz da Rocha, Isadora Filipaki; Amatuzzi, Rafaela Ferreira; Lucena, Aline Castro Rodrigues; Faoro, Helisson; Alves, Lysangela Ronalte (Frontiers in Cellular and Infection Microbiology, 2020)
The extracellular vesicle (EVs) traffic has been highlighted as a very important pathway of cellular communication. EVs are produced by prokaryotes and eukaryotes organisms and can carry molecules to help maintain homeostasis, responding to general disbalance, infections, and allowing rapid modulation of the immune system. In the context of infection, EVs from both the host and the pathogen have been identified as playing roles in the recruitment of immunological molecules that can lead to the resolution of the infection or the host’s defeat. Bacterial vesicles RNA cargo play roles in the host cell by regulating gene expression and modulating immune response. In fungi the RNA molecules present in EVs are diverse and participate in communication between the host and pathogenic fungi. Little is known about how cross-kingdom sRNA trafficking occurs, although in recent years, there has been an increase in studies that relate EV participation in sRNA delivery. This review aims to elucidate and update the reader concerning the role of extracellular vesicles, with emphasis in the RNA content. We describe the EVs during infection from the host point-of-view, as well as the bacteria and fungi pathogens producing EVs that help the establishment of the disease.